Photocatalytic degradation of methylene blue Using N-doped ZnO/carbon dot (N-ZnO/CD) nanocomposites derived from organic soybean - Ayu, Dinda Gusti (2023)
This study reports on successful synthesis of carbon dots (CDs), nitrogen-doped zinc oxide (N-ZnO), and N-ZnO/CD nanocomposites as photocatalysts for degradation of methylene blue. The first part was the synthesis of CDs utilizing a precursor from soybean and ethylenediamine as a dopant by a hydrothermal method. The second part was the synthesis of N-ZnO with urea as the nitrogen dopant carried out by a calcination method in a furnace at 500 °C for 2 h in an N2 atmosphere (5 °C min-1). The third part was the synthesis of N-ZnO/CD nanocomposites. The characteristics of CDs, N-ZnO, and N-ZnO/CD nanocomposites were analyzed through Fourier transform infrared (FTIR), UV-vis absorbance, photoluminescence (PL), high-resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), thermal gravimetry analysis (TGA), field-emission scanning electron microscopy energy-dispersive spectroscopy (FESEM EDS), X-ray photoelectron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) analysis. Based on the HR-TEM analysis, the CDs had a spherical shape with an average particle size of 4.249 nm. Meanwhile, based on the XRD and HR-TEM characterization, the N-ZnO and N-ZnO/CD nanocomposites have wurtzite hexagonal structures. The materials of N-ZnO and N-ZnO/CD show increased adsorption in the visible light region and low energy gap E g. The E g values of N-ZnO and N-ZnO/CDs were found to be 2.95 and 2.81 eV, respectively, whereas the surface area (S BET) values 3.827 m2 g-1 (N-ZnO) and 3.757 m2 g-1(N-ZnO/CDs) belonged to the microporous structure. In the last part, the photocatalysts of CDs, N-ZnO, and N-ZnO/CD nanocomposites were used for degradation of MB (10 ppm) under UV-B light irradiation pH = 7.04 (neutral) for 60 min at room temperature. The N-ZnO/CD nanocomposites showed a photodegradation efficiency of 83.4% with a kinetic rate of 0.0299 min-1 higher than N-ZnO and CDs. The XRD analysis and FESEM EDS of the N-ZnO/CDs before and after three cycles confirm the stability of the photocatalyst with an MB degradation of 58.2%. These results have clearly shown that the N-ZnO/CD nanocomposites could be used as an ideal photocatalytic material for the decolorization of organic compounds in wastewater.